A Bibliometric Analysis of Job-Hopping Among Millennials in theWorkplace (West Science Business and Management, 2025)
Job-hopping has become a prevalent phenomenon among millennials in the workplace, driven by factors such as career advancement, job satisfaction, compensation, and organizational culture. This study employs bibliometric analysis to explore research trends on jobhopping among millennials, examining 317 publications from 1912 to 2024. By utilizing bibliometric indicators and visualization tools such as VOSviewer, this research identifies key themes, influential studies, and emerging research gaps in the field. The findings reveal a significant increase in scholarly interest in job-hopping since 2015, highlighting its impact on employee retention strategies, workforce mobility, and organizational performance. The study also highlights the role of digital transformation and generational work preferences in shaping job-hopping behaviours. The insights from this research contribute to academic literature and provide practical implications for organizations in designing effective retention strategies tailored to the millennial workforce.